Mistake and non-disclosure of fact : models for English contract law - Beale, H. G. (Oxford : Oxford University Press, 2012)
English law seldom gives relief when a party to a contract finds that she has entered the contract under a serious mistake about the subject matter or the facts. This book argues that small businesses suffer as a result, and proposes possible solutions including adopting the proposed Common European Sales Law.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on Aug. 24, 2012).
Keywords: Contracts -- England; Contracts -- Wales